Treated dentin matrix particles combined with dental follicle cell sheet stimulate periodontal regeneration. Issue 9 (September 2019) - Yang, Hefeng; Li, Jie; Hu, Yu; Sun, Jingjing; Guo, Weihua; Li, Hui; Chen, Jinglong; Huo, Fangjun; Tian, Weidong; Li, Song
Abstract: Objective: Periodontal tissue engineering is an attractive approach for restoring periodontal-supporting structures and functions. However, complete periodontal regeneration has not been accomplished. Previous studies demonstrated the feasibility of using cell sheets and treated dentin matrix (TDM) to regenerate bio-roots. Methods: In this study, we regenerated periodontal tissue using cell sheets combined with TDM particles (TDMPs). Human dental follicle cells (hDFCs) were isolated and characterized. Human dental follicle cells sheets (hDFCSs) and human TDMPs (hTDMP) were fabricated and characterized. The osteogenic effect of hTDMP was evaluated on human bone marrow stromal cells (hBMSCs) in vitro and a rat calvarial bone defect in vivo . Real-time PCR, western blotting, radiograph analysis, and histological analysis were performed to evaluate the periodontal induction capacity of hTDMP. One-wall periodontal intrabony defects were prepared to evaluate the periodontal regeneration capacity of TDMP/DFCSs on beagle dogs. Results: The results showed that hDFCs were mesenchymal stem cells. hTDMP promoted the proliferation and osteogenic differentiation of hBMSCs. New bone formation was observed in the rat calvarial bone defect zone in both the hTDMP and hydroxyapatite/β-tricalcium phosphate groups. Periodontal-like tissues showed better regeneration in the canine TDMP + DFCS group than in the other groups. Significance: These results demonstrate the potential of using TDMP/DFCSs in periodontal regeneration.